Formulation and Characterization of Bromocriptine Mesylate as Liquid Self-Nano Emulsifying Drug Delivery System - Zainab A. Hussein; Nawal A. Rajab (College of Pharmacy University of Baghdad, 2018)
Bromocriptine mesylate is a semisynthetic ergot alkaloid derivative with potent dopaminergic activity, used in the treatment of pituitary tumors, Parkinson's disease (PD), hyperprolactinaemia, neuroleptic malignant syndrome, and type 2 diabetes ,the oral bioavailability is  approximately 6%, therefore aim  its  prepare and evaluate bromocriptine mesylate  as liquid self nano emulsifying drug delivery system to enhance its solubility , dissolution and stability . Solubility study was made in different vehicles to select the best excipients for dissolving bromocriptine mesylate. Pseudo-ternary phase diagrams were constructed at 1:1, 2:1, 3:1 and 4:1 ratios of surfactant and co-surfactant, four formulations were prepared using various concentrations of castor oil, tween 80 and ethanol. All prepared formulations were evaluated for particle size distribution, polydispersity index, drug content, thermodynamic stability, dispersibility and emulsification time, robustness to dilution and in vitro drug dissolution. It was found that release rate and extent for all prepared formulations were significantly higher (p < 0.05) than plain drug powder. from the study, it was concluded that self-nanoemulsifying drug delivery system is a promising approach to improve solubility, dissolution, and stability of bromocriptine mesylate.